1986
DOI: 10.1039/f19868201007
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of pentasil zeolite catalysts using ozone and oxygen

Abstract: A novel procedure for the removal of carbonaceous deposits from zeolites using ozone-enriched oxygen is described. Pentasil zeolites (SiO,/Al,O, mole ratios 35, 70) were studied and deactivated using methanol conversion to hydrocarbons and o-xylene isomerisation. Low temperature ozone reactivation was found to restore the catalyst activity for these reactions and hence can be considered as an alternative procedure to high temperature oxygen reactivation currently utilised industrially. Ozone reactivation was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…1107 Alternatively, regeneration by ozone is an attractive low temperature process for coke removal due to the high oxidizing activity of this compound. [1112][1113][1114][1115] For instance, Copperthwaite et al 1113 showed that an ozone-enriched oxygen treatment could restore activity of deactivated ZSM-5 zeolite under mild conditions (150 °C), while a temperature of about 450 °C was necessary with oxygen only.…”
Section: Catalyst Regenerationmentioning
confidence: 99%
“…1107 Alternatively, regeneration by ozone is an attractive low temperature process for coke removal due to the high oxidizing activity of this compound. [1112][1113][1114][1115] For instance, Copperthwaite et al 1113 showed that an ozone-enriched oxygen treatment could restore activity of deactivated ZSM-5 zeolite under mild conditions (150 °C), while a temperature of about 450 °C was necessary with oxygen only.…”
Section: Catalyst Regenerationmentioning
confidence: 99%
“…Owing to its strong oxidizing properties, O3 can remove coke from catalysts at a much lower temperature (50-200 °C) [18,[58][59][60][61]. Copperthwaite et al [58] showed that regeneration with ozone-enriched oxygen (O3/O2 mole ratio of 0.05) restored the catalytic activity of deactivated ZSM-5 methanol conversion catalysts at 150 °C in 90 min. Compared to O2 reactivation a slightly increased lifetime but reduced initial methane yield were observed.…”
Section: Ozone/oxynitride Oxidationmentioning
confidence: 99%
“…Typically, alternative approaches have focused on faster treatments at lower temperatures such as ozone [7,8] or non-thermal plasma [9,10], to cite the most successful examples. Liquidphase treatments requiring simpler hardware and mild conditions are hardly reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%